Avaliação da relação entre as queixas e os agravos à saúde dos cortadores de cana de açúcar que buscam atendimento médico em serviço público de emergência (estudo de caso realizado em município da região de São José do Rio Preto SP) - Custodio, Wilson José (Universidade Federal de São Carlos, 2013)
This work aims to perform the analysis of complaints made by workers within the sugar cane cutting business and their correlation with clinical outlook during the emergency care in a public health unit and its relationship to work in the cane. The results found from the survey of the medical records, the laboratory tests, and the interviews with the workers, present the relationships between diagnoses and characteristics of the work process, in addition to determining the absence of care protocol directed to such worker, whom does not find in the public health system of which it is to him constitutionally guaranteed. The disorders related to the work/health relationship and the conditions found that it should allow for redemption of its homeostasis are presented here in order to provoke thought about this dissonance.
Keywords: Engenharia de produção; Corte manual da cana-de-açúcar; Desgaste físico; Trabalho rural; Cortador de cana-de-açúcar; Saúde do trabalhador; Sugar cane cutter; Manual cutting; Wear and tear; Worker health; Rural work; ENGENHARIAS::ENGENHARIA DE PRODUCAO